Assessing age related morphological variations of Rousettus aegyptiacus (E. Geoffroy St.-Hilaire, 1810) in Durba, Democratic Republic of Congo, and Ga Mafefe, South Africa - Kearney, Teresa (University of Pretoria, 2024)
Thesis (PhD (Zoology))--University of Pretoria, 2024.